Ostracism and the EU's contradictory approach to sanctions at home and abroad. Issue 4 (8th August 2019) - Hellquist, Elin
ABSTRACT: The European Union (EU) is one of the world's most active imposers of foreign policy sanctions. By contrast, the EU has never used formal political sanctions against a member. Why does the EU favour sanctions as an instrument to deal with norm violations abroad, but not at home? The article argues that an understanding of sanctions as ostracism helps illuminate this discrepancy. Far from technical instruments that can be made to 'work' through improved design, sanctions are social instruments that operate through selective exclusion. An in-depth scrutiny of public justifications from the European institutions and individual politicians shows that both at home and abroad sanctions are strongly associated with ostracising attributes. However, whereas practical and symbolic distance-taking from the target is core for foreign policy sanctions, at home, the same ostracising properties run against the EU's traditional insistence on resolving disagreements through rational dialogue.